A comparative study on the regulations of anabolic steroids in domestic use: between Malaysia and United Kingdom / Mohamad Asif Mohd Noor … [et al.] - Mohd Noor, Mohamad Asif; Afiq Zulkufly, Muhammad Azizul; Mohd Azlan, Siti Nurazleen; Nazifa Azhar, Nurul Lydia (2014)
This research has been conducted to analyse the existing legal enforcement in Malaysia governing the use, sale and distribution of anabolic steroids, where, special references have been made to the legal position in United Kingdom. This research aims to examine the adequacy of the existing law Poison Act 1952, Sale of Drugs Act 1952 and Control of Drugs and Cosmetic Regulations 1984 which are ought to be revised in order to handle cases that involves in illegal use and illicit sale and distributions of anabolic steroids. This study also reveals how currently in Malaysia there exist no specific law that focuses on illegal personal use of anabolic steroids and how its enforcement are given very little attention upon. The continuing evolution of the trend of gaining a well-developed aesthetic physical appearance is the main drive that contributes to the demand the anabolic steroids from the market, which in a way leads to a rampant illicit distribution and sale throughout the country. Thus, a comparative study between, Malaysia and United Kingdom has been carried out in this study to determine the present parameters of the law and its enforcement of the illegal use, and illicit sale and distributions.